2020
DOI: 10.1038/s41598-020-75252-w
|View full text |Cite
|
Sign up to set email alerts
|

Brief localised monocular deprivation in adults alters binocular rivalry predominance retinotopically and reduces spatial inhibition

Abstract: Short-term deprivation (2.5 h) of an eye has been shown to boost its relative ocular dominance in young adults. Here, we show that a much shorter deprivation period (3–6 min) produces a similar paradoxical boost that is retinotopic and reduces spatial inhibition on neighbouring, non-deprived areas. Partial deprivation was conducted in the left hemifield, central vision or in an annular region, later assessed with a binocular rivalry tracking procedure. Post-deprivation, dominance of the deprived eye increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…In those studies, they usually occlude one eye using a patch for 2.5 hr, and in our Experiment 2, we occluded the eye for 2 min (that was the time needed to obtain two thresholds in each session). However, in a recent study using shorter deprivation periods of 3 to 6 min, Han et al (2020) found that the deprived eye changed from spatial surround suppression before deprivation to surround facilitation afterward; no binocular conditions were tested. This raises the question of whether the lower suppression index we found in the monocular condition might reflect a similar process, with the monocular results being affected by a shift toward facilitation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In those studies, they usually occlude one eye using a patch for 2.5 hr, and in our Experiment 2, we occluded the eye for 2 min (that was the time needed to obtain two thresholds in each session). However, in a recent study using shorter deprivation periods of 3 to 6 min, Han et al (2020) found that the deprived eye changed from spatial surround suppression before deprivation to surround facilitation afterward; no binocular conditions were tested. This raises the question of whether the lower suppression index we found in the monocular condition might reflect a similar process, with the monocular results being affected by a shift toward facilitation.…”
Section: Discussionmentioning
confidence: 98%
“…Second, in Experiment 2, we allowed a recovery period of 3 min in between monocular sessions. Han et al (2020) found their effect immediately after deprivation, while Kim et al (2017) found that the effect of a 15-min deprivation had largely decayed back to baseline after 5 min of recovery. Nevertheless, we examined our data to see if we could detect any effect attributable to previous deprivation rather than monocular viewing per se.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, BR has emerged as a popular tool for studying perceptual bistability ( 6 ), predictive coding ( 7 ), neural concomitants of consciousness ( 8 ), and visual processing outside of awareness ( 9 ). BR has also been employed as a psychophysical tool for studying other aspects of human perception and cognition, including visual adaptation ( 10 ), eye dominance ( 11–13 ), mental imagery ( 14 ), spatial vision ( 15–17 ), multimodal sensory interactions ( 18–20 ), serial dependence ( 21 ), perceptual decision-making ( 22 ), and the effects of attention on visual plasticity ( 23 , 24 ). BR has also been used as a proxy for assessing GABAergic inhibition in the human brain ( 25–29 ) and as an assay for examining neural dynamics in people diagnosed with psychiatric disorders ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of binocular rivalry provide an elaborated measure of ocular dominance, more quantitative and precise ( Ooi & He, 2020 ) than other sighting eye dominance tests, such as the Porta test ( Porta, 1593 ; Lederer, 1961 ) or the hole in card test ( Durand & Gould, 1910 ). For example, binocular rivalry made it possible to unveil a form of plasticity in adult humans, consisting of an ocular dominance shift after a brief period (approximately 2 hours) of monocular deprivation ( Lunghi, Burr, & Morrone, 2011 , 2013 ; Han, Alais, MacDougall, & Verstraten, 2020 ; Wang, McGraw, & Ledgeway, 2020 ).…”
Section: Introductionmentioning
confidence: 99%